2020
DOI: 10.3390/su13010089
|View full text |Cite
|
Sign up to set email alerts
|

Drivers for Universities’ Contribution to the Sustainable Development Goals: An Analysis of Spanish Public Universities

Abstract: Universities have a critical role in achieving the Sustainable Development Goals (SDGs), both for implementing active policies and for encouraging other actors to participate. This requires having the skills and mind-sets to contribute to these challenges. The relevance and the commitment of universities to sustainability has led to the inclusion of SDGs in the strategies and agendas of these institutions. This requires the involvement of all the actors and some structural and cultural changes that put SDGs at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 34 publications
(57 reference statements)
3
72
0
4
Order By: Relevance
“…They are therefore central to global sustainable development. In line with this, Blasco, Brusca and Labrador [26]…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…They are therefore central to global sustainable development. In line with this, Blasco, Brusca and Labrador [26]…”
Section: Discussionsupporting
confidence: 69%
“…They are central to global sustainable development. In line with this, Blasco, Brusca and Labrador [26] state that universities have embraced the SDGs in their research and from multiple perspectives. The transfer of knowledge and pedagogical development involves the inclusion of the SDGs in university curricula and in the teaching guides aimed at academic staff.…”
Section: Discussionmentioning
confidence: 79%
“…We need to keep in mind that not all HEIs operate and internationalize in similar ways, but many of the activities and structures proposed in this article (institutional initiatives, international research and partnerships, mobility, global citizenship education, professional development, and declarations signed through networks or alliances) can be applied to an institution's internationalization efforts and plans (Figure 2). Increasing visibility of an institution on the internet through research and partnerships has shown to be a key determinant of SDGs advancement and has led to increased internationalization, government investment in research and infrastructure, and higher revenues per student (Blasco et al, 2021). These results are not surprising, as internationalization hinges on partnerships abroad and can thrust sustainable development, especially in SDG17 (Partnerships for the Goals).…”
Section: Reorienting Institutional Initiatives To Support Internationalization and The Sdgsmentioning
confidence: 99%
“…Among a great range of fields involving ESD, this paper focus on the stakeholder analysis in the context of ESD in a typical Chinese university and Sino-foreign university. Universities are leaders in education, research, and innovation [2]. They have a crucial role in promoting students' perception of sustainable development to grow as a sustainable development leader and support the transformation of sustainable societies [3].…”
Section: Introductionmentioning
confidence: 99%